Shopaholic to the rescue : a novel - Kinsella, Sophie (Kinsella, Sophie. Shopaholic series, 2015)
"Becky's father Graham and her best friend's husband, Tarquin, have disappeared from Los Angeles saying simply they have "something to take care of." But Tarquin's wife Suze who is Becky's best friend, and Becky's mother Jane, are convinced the two men are hiding something and are in danger--their imaginations run wild. They must track them down! Hijinks ensue as husband Luke drives Becky, daughter Minnie, Jane, Suze and other favorite Kinsella characters across country from LA to Las Vegas in search of the missing men. Becky feels deeply guilty about ignoring her father while he was in LA, in addition Becky feels her enemy Alicia is threatening her friendship with Suze. "--